Customer Behavior and the Effect of Internet Advertising Study (With Special Reference to E-mails) - SMITHA KOTHARI (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Many prominent advertisers have been coming up with a net broadcast replica. They propose to harmonize the net and TV advertising. In actuality, their objective is to progress upon TV publicity by combining both the interactive advantages of communicwithation with the full visual effect of broadcast. Marketers struggle to design their advertisements extra engaging. Consumers can contribute more to online advertisements as they get the bulk of the proposal. Brand attitudes are influenced by interactions during this engagement. The significant trend is that advertisers are trying out novel formats, such as video games and interactive product demos in new formats like pop-up windows, child windows, and side frames, and that web advertising is shifting away from the banners.